Alternative ‘block and delivery’ approach for alcohol septal ablation in hypertrophic cardiomyopathy with ischemia: a case report - S. M. Mamun Iqbal; Neuton Mondal; Mafuza Tabassum Khan; Ashir Faishal Hamim; Nurullah Mujahid Majumder; Anindita Das Barshan; Mohammad Jahid Hasan (The Egyptian Heart Journal)
Abstract Background Hypertrophic cardiomyopathy (HCM) is a prevalent hereditary cardiac disorder characterized by marked myocardial hypertrophy, which may lead to impaired diastolic function and relative myocardial ischemia. On rare occasions, HCM coexists with coronary artery disease (CAD), complicating therapeutic decisions due to heightened risks of heart failure and ischemic events. Treatment options for these patients commonly include surgical myomectomy or alcohol septal ablation, traditionally performed using an over-the-wire (OTW) balloon catheter. Here, we present a case in which a modified 'block and delivery' alcohol septal ablation technique was utilized, instead of the conventional OTW approach, in a patient with concurrent HCM and CAD within a resource-limited setting. Case presentation A 40-year-old Asian female presented with angina and acute heart failure in our clinic. Diagnostic evaluations revealed hypertrophic obstructive cardiomyopathy (HOCM) with severe left ventricular outflow tract obstruction (LVOTO) and significant coronary artery stenosis. Due to equipment constraints, the patient underwent staged interventions: a percutaneous coronary intervention (PCI) followed by alcohol septal ablation using a modified technique. This intervention effectively reduced the LVOT gradient from 108 to 17 mmHg. At the one-year follow-up, the patient demonstrated good health, complete symptom resolution, and a normal left ventricular outflow tract gradient. Conclusion This case illustrates the feasibility of employing a modified alcohol septal ablation technique in resource-limited settings, highlighting the importance of adaptable and innovative approaches in managing complex cardiac conditions.